2021
DOI: 10.1177/23312165211054924
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Resolution of Late Reverberation in Virtual Acoustic Environments

Abstract: Late reverberation involves the superposition of many sound reflections, approaching the properties of a diffuse sound field. Since the spatially resolved perception of individual late reflections is impossible, simplifications can potentially be made for modelling late reverberation in room acoustics simulations with reduced spatial resolution. Such simplifications are desired for interactive, real-time virtual acoustic environments with applications in hearing research and for the evaluation of hearing suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…In addition to being compatible with arbitrary geometry, a benefit of the generalized approach over the shoebox approach is the gradually increasing ILD for six VRS and a performance for 12 VRS, which is generally more similar to 96 VRS. The results of the current technical evaluation support the perceptual evaluation in [33] showing that 24 VRS are sufficient for rendering anisotropic late reverberation in the tested conditions.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…In addition to being compatible with arbitrary geometry, a benefit of the generalized approach over the shoebox approach is the gradually increasing ILD for six VRS and a performance for 12 VRS, which is generally more similar to 96 VRS. The results of the current technical evaluation support the perceptual evaluation in [33] showing that 24 VRS are sufficient for rendering anisotropic late reverberation in the tested conditions.…”
Section: Resultssupporting
confidence: 78%
“…Although an isotropic late reverberant field is approximated in the case of a completely homogeneous distribution of absorption coefficients at all boundaries, a more critical case regarding spatial resolution of late reverberation occurs for inhomogenously distributed absorption coefficients and in the case of coupled (sub-) volumes with connecting openings. Such a critical test case was assessed in [33], using a spatial mapping method for inhomogeneous boundary conditions in shoebox shaped rooms [34]. They have shown that 12-24 VRS are perceptually sufficient in a single room with anisotropic late reverberation, depending on the stimulus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having a virtual acoustic rendering of complex acoustic environments, will allow to specifically manipulate auditory cues to get a better understanding about their relevance. Factors such as conservation of spatial Interaural Time Delay (ITD), Interaural Level Difference (ILD), and Inter Aural Cross Correlation (IACC) cues in binaural hearing aids can be investigated in relevant daily-life settings (e.g., [67,68]). Whereas ITD and ILD cues are relevant for the perceived location of sound sources, IACC influences the perceived width of a sound source.…”
Section: Future Relevance For Hearing Researchmentioning
confidence: 99%